Pfade in die Krise Der Einfluss des Faktors Familie auf die Genese und Dynamik strategischer Pfadabhängigkeit in Familienunternehmen - Treiber, Thomas (2018)
Why is it so diffcult for companies like Schlecker to leave once chosen paths of strategic development at the right time, and to rearrange their strategies when faced with new environmental challenges? This paper shows with a perspective on organizational path dependence theory how economic und social mechanisms might favour the reproduction of established strategies - and at the same time complicate leaving the strategical development paths even more. The part of familial influence on decision processes is researched and the factor of family in the formation of strategic path dependence is inquired based on qualitative case studies.